The Role of Flavonoids as Immunomodulatory Agents: Therapeutic Potential and Mechanisms of Action - Sabini, Jasmine Harumi; Susilowati, Rina Priastini; Sari, Monica Puspa (Universitas Kristen Krida Wacana, 2025)
Flavonoids are a group of polyphenolic compounds widely found in plants and have long been recognized for their biological activities, including antioxidant and anti-inflammatory effects. In recent years, increasing attention has been given to the potential of flavonoids as immunomodulatory agents. This review article aims to summarize and evaluate scientific evidence regarding the role of flavonoids in modulating both innate and adaptive immune responses. Several flavonoids, such as apigenin, genistein, quercetin, and naringenin, have been shown to suppress the production of proinflammatory cytokines, inhibit macrophage activation, and influence the differentiation of T cell subpopulations such as Th1, Th2, Th17, and Treg. In addition, some flavonoids have been found to inhibit inflammasome activation and may promote macrophage polarization toward either the M1 or M2 phenotype depending on the pathological context. Although preclinical data demonstrate promising results, challenges such as low bioavailability remain a major barrier to therapeutic application. Therefore, further research is needed to optimize the clinical potential of flavonoids as effective and safe immunomodulatory agents.